Description of the Level of Public Knowledge Regarding the Use of the JKN Mobile Aplication - Riski Aryanti; Pradea Wulandari (GLOBAL HEALTH SCIENCE GROUP, 2025)
The National Health Insurance (JKN) is a government program that provides financial protection for the people of Indonesia to meet their basic healthcare needs. To improve services for the public, BPJS has introduced the Mobile JKN application. This application facilitates participants in obtaining information and administrative services related to the National Health Insurance program by utilizing information technology through a smartphone app that can be downloaded from the Play Store and App Store. Observations conducted by the researcher in RT 16 showed that out of 12 participants are still not fully familiar with the use of the Mobile JKN application. Based on preliminary studies conducted by the researcher on 10 JKN participants in RT 16, it was found that 6 participants (60%) were unaware of how to use the Mobile JKN application. Meanwhile, 4 participants (40%) knew how to use the Mobile JKN application but preferred to visit Primary Health Facilities (FKTP) instead, citing difficulties in understanding and registering for the Mobile JKN application initially. Currently, everything related to healthcare services, especially JKN, must be accessed through gadgets, starting from registration and beyond. This research is important because some JKN participants have been found to not fully understand the use and benefits of the Mobile JKN application. If the public lacks understanding of this application, it may hinder healthcare services, which now require the use of the Mobile JKN application. the aim of this research is to determine the level of knowledge of the rt 16 kelurahan klandasan ulu, about the use of the jkn mobile application. The research method used in this study is quantitative descriptive research with a cross-sectional approach. This research method is employed to provide an overview of the public’s level of knowledge regarding the use of the Mobile JKN application. Data collection in this study was conducted using questionnaires and analyzed using bivariate analysis. Based on the results of the research and discussion with 47 JKN participants regarding the level of knowledge in RT 16 on the use of the Mobile JKN application is at a good level. The results show that out of 47 respondents, 53% had good knowledge about using the Mobile JKN application, while 47% had poor knowledge.